2003
DOI: 10.1002/ange.200350913
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Induced Micelle to Vesicle Transition in the Sodium Dodecylsulfate/Dodecyltriethylammonium Bromide System

Abstract: Ein schrittweiser Übergang von zylindrischen Micellen zu Vesikeln wird im kationisch‐anionischen Tensidsystem Natriumdodecylsulfat/Dodecyltriethylammoniumbromid durch Temperaturerhöhung herbeigeführt. Dieser Übergang wurde durch dynamische Lichtstreuung, Elektronenmikroskopie von Gefrierbrüchen sowie rheologische Messungen untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…In the case of particles in a solvent, the analysis of the time-dependent scattered intensity provides a measure of the diffusion coefficient, and consequently of the hydrodynamic size of the particles, and information about the formation of various types of aggregates. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Nowadays, it is also a very common tool to determine particle size. [58,59] Most of the studies were, however, performed in aqueous media and only a few papers reported measurements performed in organic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of particles in a solvent, the analysis of the time-dependent scattered intensity provides a measure of the diffusion coefficient, and consequently of the hydrodynamic size of the particles, and information about the formation of various types of aggregates. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Nowadays, it is also a very common tool to determine particle size. [58,59] Most of the studies were, however, performed in aqueous media and only a few papers reported measurements performed in organic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…For conventional amphiphiles, [26] such as ionic surfactants, the temperature sensitive vesicle-to-micelle transitions are attributed to the increasing solubility of the counterion upon increasing the temperature. For nonionic surfactants, temperature-induced micelle-to-vesicle transitions are well known, which is attributed to a decrease in head-group hydration upon increasing the temperature.…”
mentioning
confidence: 99%
“…B. Temperatur, [45] Konzentration, [46] der Zusammensetzung des Lçsungsmittels, [47] der molekularen Struktur und Form der Bausteine, [14a, 30] sterischen Wechselwirkungen einzelner Molekülteile und der Anwesenheit bestimmter Additive, [48] sowie vom relativen Verhältnis von hydrophoben und hydrophilen Molekülteilen. Die Bildung unterschiedlicher Aggregatformen sowie deren Grçße hängt von zahlreichen Faktoren ab, wie z.…”
Section: Perylenbisimidverbände In Wasserunclassified
“…[43] Das mit Dendronen der ersten Generation versehene Bolaamphiphil zeigt dabei wiederum die typischen Merkmale aggregierter PBIs, ein breites Absorptionsspektrum mit hypsochrom verschobenem Absorptionsmaximum und schwache Fluoreszenz. Beim symmetrischen PBI mit den Dendronsubstituenten der zweiten Generation (13) [45] Konzentration, [46] der Zusammensetzung des Lçsungsmittels, [47] der molekularen Struktur und Form der Bausteine, [14a, 30] sterischen Wechselwirkungen einzelner Molekülteile und der Anwesenheit bestimmter Additive, [48] sowie vom relativen Verhältnis von hydrophoben und hydrophilen Molekülteilen. [9,49] [53] Des Weiteren fand dieses positiv geladene PBI durch elektrostatische Selbstorganisation mit negativ geladenen Polyelektrolyten in Dünnschichten Anwendung.…”
Section: Perylenbisimidverbände In Wasserunclassified